Do employers use unemployment as a sorting criterion when hiring? Evidence from a field experiment - Stefan Eriksson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2011)
In this paper, we use unique data from a field experiment in the Swedish labor market to investigate how past and contemporary unemployment affect a young worker's probability of being invited to a job interview. In contrast to studies using registry/survey data, we have complete control over the information available to the employers and there is no scope for unobserved heterogeneity. We find no evidence that recruiting employers use information about past unemployment to sort workers, but some evidence that they use contemporary unemployment to sort workers. The fact that employers do not seem to use past unemployment as a sorting criterion suggests that the scarring effects of unemployment may not be as severe as has been indicated by previous studies.
urn:nbn:de:101:1-201202285043
Keywords: J64; 330; scarring; unemployment; field experiment; Arbeitsnachfrage; Personalauswahl; Arbeitslosigkeit; Jugendarbeitslosigkeit; Feldforschung; Schweden